Contributions of the Endothelium to Vascular Calcification - Zhang, Li; Yao, Jiayi; Yao, Yucheng; Boström, Kristina I. (Frontiers in Cell and Developmental Biology, 2021)
Vascular calcification (VC) increases morbidity and mortality and constitutes a significant obstacle during percutaneous interventions and surgeries. On a cellular and molecular level, VC is a highly regulated process that involves abnormal cell transitions and osteogenic differentiation, re-purposing of signaling pathways normally used in bone, and even formation of osteoclast-like cells. Endothelial cells have been shown to contribute to VC through a variety of means. This includes direct contributions of osteoprogenitor cells generated through endothelial-mesenchymal transitions in activated endothelium, with subsequent migration into the vessel wall. The endothelium also secretes pro-osteogenic growth factors, such as bone morphogenetic proteins, inflammatory mediators and cytokines in conditions like hyperlipidemia, diabetes, and renal failure. High phosphate levels caused by renal disease have deleterious effects on the endothelium, and induction of tissue non-specific alkaline phosphatase adds to the calcific process. Furthermore, endothelial activation promotes proteolytic destruction of the internal elastic lamina that serves, among other things, as a stabilizer of the endothelium. Appropriate bone mineralization is highly dependent on active angiogenesis, but it is unclear whether the same relationship exists in VC. Through its location facing the vascular lumen, the endothelium is the first to encounter circulating factor and bone marrow-derived cells that might contribute to osteoclast-like versus osteoblast-like cells in the vascular wall. In the same way, the endothelium may be the easiest target to reach with treatments aimed at limiting calcification. This review provides a brief summary of the contributions of the endothelium to VC as we currently know them.